Teriflunomide and Epstein–Barr virus in a Spanish multiple sclerosis cohort: in vivo antiviral activity and clinical response - Domínguez-Mozo, María Inmaculada; González-Suárez, Inés; Villar, Luisa María; Costa-Frossard, Lucienne; Villarrubia, Noelia; Aladro, Yolanda; Pilo, Belén; Montalbán, Xavier; Comabella, Manuel; Casanova-Peño, Ignacio; Martínez-Ginés, María Luisa; García-Domínguez, Jose Manuel; et al. (Frontiers in Immunology, 2023)
Background Epstein-Barr virus (EBV) and Human herpesvirus 6 (HHV-6) have been associated with multiple sclerosis (MS). Teriflunomide is an oral disease modifying therapy approved for treatment of relapsing forms of MS. In the preclinical Theiler's Murine Encephalitis Virus model of MS, the drug demonstrated an increased rate of viral clearance versus the vehicle placebo. Furthermore, teriflunomide inhibits lytic EBV infection in vitro. Objective 1. To evaluate the humoral response against EBV and HHV-6 prior teriflunomide treatment and six months later. 2. To correlate the variation in the humoral response against EBV and HHV-6 with the clinical and radiological response after 24 months of treatment with teriflunomide. 3. To analyze the utility of different demographic, clinical, radiological and environmental data to identify early biomarkers of response to teriflunomide. Methods A total of 101 MS patients (62 females; mean age: 43.4 years) with one serum prior to teriflunomide onset and another serum sample 6 months later were recruited. Eighty had been treated at least 24 months, 13 had stopped teriflunomide before 24 months and 8 were currently under teriflunomide therapy but with less than 24 months of follow-up. We analyzed the levels of the viral antibodies titers above mentioned in serum samples with ELISA commercial kits, and the levels of serum neurofilament light chain (Nf-L). Results Antiviral antibody titers decreased for EBNA-1 IgG (74.3%), VCA IgG (69%), HHV-6 IgG (60.4%) and HHV-6 IgM (73.3%) after six months of teriflunomide. VCA IgG titers at baseline correlated with Nf-L levels measured at the same time (r=0.221; p=0.028) and 6-months later (r=0.240; p=0.017). We found that higher EBNA-1 titers (p=0.001) and a higher age (p=0.04) at baseline were associated with NEDA-3 condition. Thus, 77.8% of patients with EBNA-1 >23.0 AU and >42.8 years (P50 values) were NEDA-3. Conclusion Treatment with teriflunomide was associated with a reduction of the levels of IgG antibody titers against EBV and HHV-6. Furthermore, higher EBNA-1 IgG titers prior to teriflunomide initiation were associated with a better clinical response.